2016
DOI: 10.1007/s11060-016-2083-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-oncology family caregivers are at risk for systemic inflammation

Abstract: Background Prolonged periods of family caregiving can induce stress levels that may negatively influence caregiver health. However, the physiologic effect of psychological distress in oncology family caregivers has received little attention. Therefore we aimed to determine longitudinal profiles of inflammatory cytokines (IL-6 and IL-1ra) in neuro-oncology caregivers and identify associations between psychological distress and cytokine levels. Methods Depressive symptoms, anxiety, caregiver burden and blood w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…For instance, Rohleder et al analyzed salivary biomarkers of caregivers of patients with cancer, finding marked changes in neurohormonal and inflammatory processes within the first year of caregiving. Likewise, Sherwood et al found higher levels of proinflammatory cytokines in male caregivers. Not surprisingly, caregivers perceiving higher levels of caregiver burden have a higher possibility of being diagnosed with stroke and an increased mortality rate .…”
Section: Resultsmentioning
confidence: 94%
“…For instance, Rohleder et al analyzed salivary biomarkers of caregivers of patients with cancer, finding marked changes in neurohormonal and inflammatory processes within the first year of caregiving. Likewise, Sherwood et al found higher levels of proinflammatory cytokines in male caregivers. Not surprisingly, caregivers perceiving higher levels of caregiver burden have a higher possibility of being diagnosed with stroke and an increased mortality rate .…”
Section: Resultsmentioning
confidence: 94%
“…However, such consequences are not limited to older caregivers, but may be more apparent in those reporting high burden, or during specific stressful periods. For example, increased inflammatory cytokines have been shown to be specific to males with anxiety, high BMI, disrupted schedules, ages 30-39 years with high burden [12] and those with high grief in the presence of blame and anger [13] or in the 6-months post-diagnosis of a child with cancer in caregiving mothers [14], a particularly stressful period. In support of this idea about stressful time periods, not all markers of inflammation were raised among long-term caregivers [15] and in caregivers with low caregiving burden allostatic load (incorporating inflammatory markers) was lower than non-caregivers [16]; potentially indicating lower distress at less stressful periods.…”
Section: Caregiving and Inflammationmentioning
confidence: 99%
“…Sherwood et al (2016) study focuses on younger caregivers of cancer patients and shows an important link with caregiving stress and inflammation as well as showing that caregiving effects are not homogeneous but that effects may relate to specific behavioural and emotional responses such as anxiety, or life disruption. Walsh et al (2018) are the first to demonstrate that chronic stress influences the development of glucocorticoid resistance by downregulating the sensitivity of glucocorticoid receptors, which corresponded with changes in psychological distress.…”
mentioning
confidence: 99%
“…Caregivers of patients with brain metastases not only acquire new care demands while facing the increasing intensity of existing demands, but also deal with physical and cognitive deterioration of their loved ones (Gerstenecker et al, 2014;Vaughan, 2012). Unfortunately, despite decades of research showing the negative emotional and physical responses of caregivers in the context of chronic illnesses (e.g., cancer, dementia), little caregiving research has been done in the field of neuro-oncology (Sherwood & Baer, 2011;Sherwood et al, 2016).…”
Section: Caregivers Of Patients With Brain Metastasesmentioning
confidence: 99%